"A ESCRITURA A ESCREVIVÊNCIA A INVENÇÃO A POEMA": PERFORMANCES E DECOLONIALIDADES NAS GRAMÁTICAS CULTURAIS DAS COLETIVAS DE POETAS PERIFÉRICAS. - Nogueira de Alencar, Claudiana (Trabalhos em Lingüística Aplicada)
The present article is the result of a theoretical-methodological proposal for a participatory and interventional research in language studies called Cultural Pragmatics (ALENCAR, 2014, 2015, 2019). It aims at establishing horizontality, the collaboration between popular and academic knowledge, through symmetrical methodologies that value different forms of life and resistance, and seek social transformation. From this perspective, I analyze the compilation of a cultural grammar of resistance by women who participate in three poets collectives on the outskirts of the city of Fortaleza (Brazil). The theoretical framework is based on the concepts of performativity of race and intersectionality according to Glenda Melo (MELO; MOITA LOPES, 2013, 2014; MELO; PAULA, 2019); on the cultural grammar and the grammar of pain as discussed in the works of Veena Das (DAS, 1995, 1999, 2007; DAS et al., 2004); on the notion of escrevivência by Conceição Evaristo (EVARISTO, 2007, 2008, 2009), and on my own research (ALENCAR, 2014, 2019). Other parts of our analytical construct are represented by the categories metapragmatics, indexicality (SILVERSTEIN, 1993, 2003), performance and entextualization (BAUMAN; BRIGGS, 1990). Investigating this subject matter I realized that the literary, cultural and political practices of these poets constitute a cultural grammar that announces a society without domination which will be created by the feminization of resistance.